Comparison of porosity assessment techniques for low-cost ceramic membranes - Maria-Magdalena Lorente-Ayza; Olga Pérez-Fernández; Raquel Alcalá; Enrique Sánchez; Sergio Mestre; Joaquin Coronas; Miguel Menéndez (Boletín de la Sociedad Española de Cerámica y Vidrio, 2017)
Several characterization methods were applied to low cost ceramic membranes developed for wastewater treatment in membrane bioreactors (MBRs) and/or tertiary treatments. The membranes were prepared by four different procedures (uniaxial pressing and extrusion, both with and without starch addition to generate pores). The pore size of these symmetric ceramic membranes was measured by two different methods: bubble point and intrusion mercury porosimetry. A good agreement between both methods was achieved, confirming the validity of the bubble point method for the measurement of the mean pore size of membranes. Air and water permeations of these ceramic membranes were also studied. The relationship between the permeation of both fluids is consistent with the ratio of viscosities, according to the Hagen–Poiseuille equation.